Fonologinė kirčio raidos baltų kalbose interpretacija - Kazlauskas, Jonas (Baltistica, 1967)
THE DEVELOPMENT OF STRESS IN THE BALTIC LANGUAGES FROM THE PHONOLOGICAL POINT OF VIEWLithuanian is a language in which not only phonetic ingredients of a sound, but also prosodic features are phonologically distinctive. There are found the following prosodic oppositions in it: according to the position of stress, according to the character of stress (falling and rising), and according to the quantity of both stressed and unstressed syllables. Both falling and rising stress can characterize any stressed long syllable. But this is characteristic not of all the Lithuanian dialects. In a considerable part of North-east Lithuania stress is connected in a certain way with quantity: only long and half-long vowels and sonants may be stressed, while short vowels and sonants are regularly unstressed: here we find only one opposition, namely, according to the place of stress. The Žemaičiai (Samogitian) dialect has preserved the opposition according to the quality of stress together with certain distinctions according to the place of stress. The three prosodic oppositions mentioned above are best preserved in the South-west Aukštaičiai dialect, the basis of the Lithuanian national language.Stress in the North-east Aukštaičiai dialects is retracted from the last on to the preceding syllable. The immediate cause of the retraction lies in the tendency to develop quantitative stress. Certain elements of quantitative stress may be found in all the Lithuanian dialects. In the West and South Aukštaičiai dialects the stressed short vowels e, a were lengthened in certain cases and at present they interchange with the unstressed short vowels e, a; cp. vē̃da (he leads) and vedù (I lead), nā̃mas (a house) and namù (with a house), vē̃lnias (a devil) and velniaĩ (devils), kā́lnas (a hill) and kalnaĩ (hills). In all the Aukštaičiai dialects the first or the second element of the stressed diphthongs is lengthened, depending upon intonation or depending upon which of them is stressed; cp. vaĩ.kas (a child) and vaikaĩ (children), vḗlnias (a devil) and velniaĩ (devils). Evidently, the stressed diphthongs begin to differ not according to intonation, but first of all according to the length of the first or the second components. Later the subsystem becomes a basic system.Dynamic stress causes the weakening of unstressed final syllables. Together with the weakening of unstressed syllables the weakening of stressed syllables takes place, which in its turn results in the absence of the lengthening of the stressed short vowel finally, though they are lengthened medially. The lengthening of the final short stressed vowels is never found in all the Lithuanian dialects, though the medial stressed short vowels are regularly or at least in certain positions. The absence of the lengthening of the stressed short vowels at the end of words together with their, lengthening in medial syllables, i.e. actually together with the rise of quantitative stress, has resulted in that not the final short syllable but the preceding long syllable is perceived as stressed. In the more northern dialects similar factors predetermine the retraction of stress even from long final syllables.In the Žemaičiai dialect the subsystem of the phonological word-stress is opposed at present to the subsystem of subphonemic delimitative word-stress whose characteristic feature is its shifting onto the preceding preposition. Synchronically it is impossible to foresee what words will have phonological word-stress and what words will have subphonemic stress, because these two types of stress are not in complementary distribution; ср. Acc. Sg. ãkẹ (eye) and Instr. Sg. àkẹ̀. It is characteristic of subphonemic word-stress that it is realized in the form of a certain phonetic syllable-stress. When a stressed syllable is followed by a long syllable, a certain phonetic syllable-stress is also characteristic of the subsystem of phonological word-stress. In the subsystem of phonological word-stress the stressed syllable has the oppositions of acute and circumflex intonations. In the subsystem of subphonemic word-stress the opposition of intonations is not found, with the exception of those dialects which show a tendency to phonologize phonetic syllable-stress. There may be observed two tendencies in the North and North-west Žemaičiai dialects: a tendency to strengthen the subsystem of phonological word-stress (in the subsystem of subphonemic stress the opposition of intonations develops in stressed syllables) and a tendency to phonologize syllable-stress. Both tendencies lead to phonological word-stress.The development of phonological word-stress in Latvian must have also been connected with the phonologization of syllable-stress.In the Žemaičiai dialect dynamic word-stress combines with musical syllable-stress and with well developed phonetic syllable-stress. Intonations are opposed here as high (acute) – low (circumflex). An attempt is made in the article to discover the possible causes of stress retraction in the Žemaičiai dialect of the Lithuanian language.We may suppose Lithuanian had at one time musical stress. Evidently words with acute syllables were opposed to words with circumflex syllables as words of high tone to words of low tone. Evidently the prehistoric realization of acute as high tone and circumflex as low tone as described above may explain certain differences in the realizations of acute on the form of falling intonation in Lithuanian and in the form of even (rising) intonations in Latvian, Prussian and the Slavonic languages: it may also explain the realization of circumflex in the form of rising intonation in Lithuanian and in the form of falling intonation in Latvian, Prussian and the Slavonic languages.